2022
DOI: 10.3390/f13122112
|View full text |Cite
|
Sign up to set email alerts
|

Different Modelling Approaches to Determine Suitable Areas for Conserving Egg-Cone Pine (Pinus oocarpa Schiede) Plus Trees in the Central Part of Mexico

Abstract: Various spatial modelling methods and tools have been used in ecology and biogeography. The application of these options serves a dual function: first, they offer information about the potential distribution of species to understand the richness and diversity of unassessed areas. Second, spatial modelling methods employ these predictions to select relevant sites to determine natural conservation areas. In this study, we compared three methods for modelling the spatial distribution of Egg-cone Pine (Pinus oocar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Similarly, MAXENT outperformed other algorithms, such as a variant of RF, BRT, and MARS, in predictions involving 171 species in both random and spatial partitioning (Valavi et al, 2023). However, a number of previous studies have reported different outcomes, which are consistent with (Barker and MacIsaac, 2022;Hysen et al, 2022;Romero-Sanchez et al, 2022). Additionally, the smaller number of areas with high residuals and lower uncertainty in the predicted habitat suitability of RF and BRT, compared to those of MARS and MAXENT in M. oculata prediction, also indicates the higher accuracy of predictions using RF and BRT.…”
Section: Impact Of Modeling Algorithms On Predictive Performancementioning
confidence: 71%
See 1 more Smart Citation
“…Similarly, MAXENT outperformed other algorithms, such as a variant of RF, BRT, and MARS, in predictions involving 171 species in both random and spatial partitioning (Valavi et al, 2023). However, a number of previous studies have reported different outcomes, which are consistent with (Barker and MacIsaac, 2022;Hysen et al, 2022;Romero-Sanchez et al, 2022). Additionally, the smaller number of areas with high residuals and lower uncertainty in the predicted habitat suitability of RF and BRT, compared to those of MARS and MAXENT in M. oculata prediction, also indicates the higher accuracy of predictions using RF and BRT.…”
Section: Impact Of Modeling Algorithms On Predictive Performancementioning
confidence: 71%
“…For instance,Barker and MacIsaac (2022) found BRT to outperform RF, MARS, and MAXENT in predictions involving virtual species;Romero-Sanchez et al (2022) found RF to achieve better performance than MAXENT in predictions for plus trees; andHysen et al (2022) found RF to perform better than MARS and MAXENT in nest predictions…”
mentioning
confidence: 99%
“…(58.9 kg ha-1 per month) [15]. Therefore, in 2019, the National Institute of Forestry, Agriculture, and Livestock Research initiated a broader research project to improve the resin production of this species in Mexico, through the selection of high-yield resin provenances and phenotypes [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…[21]. Therefore, in 2019, the National Institute of Forestry, Agriculture, and Livestock Research initiated a broader research project to improve the resin production of this species in Mexico, through the selection of high-yield resin provenances and phenotypes [22,23].…”
Section: Introductionmentioning
confidence: 99%